Geochronology and petrogenesis of the southern portion of Socorro Granitic Batholith based on U-Pb dating and isotope geochemistry - Toledo, Bárbara Bueno (2020)
The Socorro Batholith is one of the most significant granitic manifestations associated with Neoproterozoic evolution in the SE of Brazil, occupying an extensive area (~ 1,200 km2) in the southern portion of Nappe Socorro-Guaxupé (NSG). U-Pb zircon dating by SHRIMP was performed to determine the ages of the major components of the batolith, and isotopic geochemical analysis (Sr-Nd-Hf) to determine the source areas. Biotite-hornblenda high-K calcium-alkaline porphyritic granites with relatively low SiO2 contents (60 - 67%) are the bulkiest components of this and other syntectonic batholiths in NSG (Água Limpa and Pinhal Ipuiúna) and other Ribeira Belt bodies, such as the Apiaí and São Roque Domains. Three samples collected in different locations of the Socorro Batolith have similar magmatic crystallization ages, 610.1± 7.0 Ma, 608.3 ± 6.6 Ma and 610.4 ± 6.8 Ma. The \'épsilon\'Nd (t) values for these rocks range from -12.3 to - 12.9, with Nd TDM ages between 1.8-2.0 Ga, and initial ratios 87Sr/86Sr(t) between 0.7119-0.7131. Hf isotope compositions of zircons (\'épsilon\'Hf(t)) from these samples varies from -12 to -17. Similar data are observed in high K calcium alkaline granites of the São Roque Domain and Cunhaporanga Batolith. One sample of a most fractionated granite body (SiO2 > 72%, Bairro da Pedreira Pluton) was 612.4 ± 4.6 Ma, suggesting contemporary to high-K calcium-alkaline granites. On the other hand, another leucogranite body (Bocaina Pluton) peraluminous, reported in the literature as related to a younger event (\"Socoro II magmatism\"), provided a clearly older age (624.4 ± 3.6 Ma), similar to that of regional anatectic granites. Both occurrences of more evolved granites present negative \'épsilon\'Nd (t), with values of -16.16 and -16.19, Nd TDM ages between 1.9 and 2.0 Ga, 87Sr / 86Sr (t) ratio between 0.7156-0.7171, and \'épsilon\'Hf (t) with strongly negative values, with average of ~ 16 in both samples, indicating a greater contribution from ancient crustal sources. Similar isotopic data are observed in the late-orogenic bodies of the Agudos Grandes Batholith, which are possibly product of middle crust. A more fractionated leucogranite (Fazenda São Sebastião Pluton) show distinct chemistry, with high SiO2 (75%), low Th contents and \'épsilon\'Nd(t) ~ - 12. Two charnockitic rocks that show transitional contacts with granites are slightly older than this magmatism. The Socorro Charnockite has \'épsilon\'Nd(t) = -6.1, \'épsilon\'Hf(t) = -9.1 (average), 86Sr/87Sr (t) = 0.7093, and an age of 641.6 ± 4.1 Ma overlapping the ages of regional orthognaisses (partly charnockitic in character), which are considered associated with pre-colonic tectonics (related to subduction?). Atibaia Charnockite has distinct geochemical affinity (lower mg # and Sr content; higher Zr), \'épsilon\'Nd (t) = -14.1, \'épsilon\'Hf(t) = -8.9 (average), and ratio 86Sr/87Sr(t) = 0.7197, and is slightly older (633.3 ± 6.2 Ma), and may signal a different tectonic configuration at the end of the drinking period of plates, still lacking characterization.